ANALISIS RESTITUSI PADA PAJAK PENGHASILAN - Ibrani Saragi; Mila Susanti (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2021)
This study aims to analyze restitution on income tax. The data used was quantitative data, the annual report of PT ABM Investama Tbk in 2019. The results showed that income tax expense decreased by approximately $10,749,000 or 41.55% from 2018. The cash flow statement from operating activities posted a 17.94% decrease in income tax payments, or $7.21 million. Overpayment of income tax is recorded as income tax expense – now on the income statement. The estimated overpayment of tax was recorded in the estimated claims for tax refund which was deducted by the allowance for impairment losses on, resulting in the estimated claims for tax refund – net. Tax restitution followed the rules of PSAK 46 and ISAK 34. During the 2019 research year, PT ABM Investama Tbk and its subsidiaries received SKPLB on corporate income tax 2017, among others CK, SSB, Mifa and Reswara. PT ABM Investama Tbk conducted tax compensation for SKPLB receipts recorded in the correction of fiscal profit or loss and income tax payable article 21.